Ultraestrutura do nervo facial intratemporal em pacientes com paralisia facial idiopática: estudo de evidências de infecção viral - Florez, Rosangela Aló Maluza [UNIFESP] (2010)
The etiology of idiopathic peripheral facial palsy (IPFP) is still uncertain; however, some authors suggest the possibility of a viral infection. AIM: to analyze the ultrastructure of the facial nerve seeking viral evidences that might provide etiological data. MATERIAL AND METHODS: We studied 20 patients with peripheral facial palsy (PFP), with moderate to severe FP, of both genders, between 18-60 years of age, from the Clinic of Facial Nerve Disorders. The patients were broken down into two groups - Study: eleven patients with IPFP and Control: nine patients with trauma or tumor-related PFP. The fragments were obtained from the facial nerve sheath or from fragments of its stumps - which would be discarded or sent to pathology exam during the facial nerve repair surgery. The removed tissue was fixed in 2% glutaraldehyde, and studied under Electronic Transmission Microscopy. RESULTS: In the study group we observed an intense repair cellular activity by increased collagen fibers, fibroblasts containing developed organelles, free of viral particles. In the control group this repair activity was not evident, but no viral particles were observed. CONCLUSION: There were no viral particles, and there were evidences of intense activity of repair or viral infection.